Problem solving in hypertension [electronic resource] - Kennedy, Lee , 1955- (Oxford : Clinical Pub., 2009)
Suitable for physicians who routinely see patients with hypertension in clinical practice, this book presents a selection of challenging cases seen in everyday practice, highlighting learning points
1. Hypertension-general -- 2. Types of hypertension and hypotension -- 3. Lifestyle factors -- 4. Hypertension at different ages -- 5. Hypertension in special groups -- 6. Complications and emergencies -- 7. Co-morbidities and associated disorders -- 8. Secondary causes of hypertension -- 9. Drugs to treat hypertension
Description based on print version record
Includes bibliographical references and index
Keywords: Hypertension